The genesis of modern idea of sovereignty - Proleiev, Sergii; Shamrai, Viсtoriia (Sententiae, 2002)
The article analyses the development of the idea of sovereignty, which is the result of six centuries of intellectual and political development that began in the early Middle Ages. Having studied the development of this idea from the idea of the plenitudo potestatis of the papacy in Gregory VII to the idea of the sovereign individual in Locke, the authors conclude that the modern understanding of popular sovereignty and the state is a consequence of the modern idea of sovereign individuals that form a political community in the only possible way - on the basis of agreement.